Β‐cyclodextrin/poly(vinyl alcohol) hydrogels containing phenylpropionic acid and naphthylamine: dual pH‐sensitive release. Issue 6 (4th September 2013) - Lee, Mi Sun; Kim, Jin‐Chul
Abstract Hydrogel composed of β‐cyclodextrin (β‐CD) and poly(vinyl alcohol) was prepared in a strong alkaline condition using epichlorohydrin as a crosslinker. Phenylpropionic acid (PPA) and naphthylamine (NA) were loaded in the cavities of β‐CD residues to endow the hydrogel with a dual pH‐sensitive characteristic. In release experiments using fluorescein isothiocyanate‐dextran (FITC‐dextran) as a dye, PPA/NA‐loaded hydrogel exhibited an extensive release not only in acidic conditions (e.g. pH 3.0) but also in alkaline conditions (e.g. pH 9.0). PPA and NA will be highly ionized at the alkaline and the acidic pH and they could promote swelling of the hydrogel, causing an extensive release at those pH values. However, the release was suppressed at mid pH values (e.g. pH 5.0 and pH 7.4), possibly due to the formation of salt bridges between PPA− and NA+. In fact, the degree of swelling at mid pH was lower than that observed at strong acidic pH and alkaline pH. According to SEM images, the pore size and the texture compactness of hydrogels which had been subjected to swelling at different pH values could also account for the dual pH‐sensitive releases. The hydrogels exhibited dual pH sensitivities in terms of FITC‐dextran release and swelling. These hydrogels might be used as a pH‐sensitive vehicle for water‐soluble drugs. © 2013 Society of Chemical Industry